EXAMINATION OF GREEN PURCHASE INTENTION: AN EMPIRICAL STUDY IN YOKOHAMA AND YOGYAKARTA - Lucia Nurbani Kartika,; Yohanes Michael Christanto, (Journal of Innovation Research and Knowledge, 2026)
This study investigates the influence of green innovation and green advertising on green purchase intention, with social and emotional value as a mediating variable, comparing consumer behavior in Yokohama, Japan, and Yogyakarta, Indonesia. The rationale for this research lies in the increasing global concern for sustainability and the need to understand how consumers from different cultural backgrounds respond to environmentally friendly products. Using a quantitative approach with the PLS-SEM method, data were collected from 100 respondents (50 from each city) through a Likert-scale questionnaire distributed via Google Forms. The findings reveal that green advertising and green innovation significantly affect social and emotional value in both cities. However, only green innovation significantly influences green purchase intention in Yokohama, while social and emotional value has a significant effect on green purchase intention in Yogyakarta. The study highlights cultural variations in environmental attitudes and emphasizes the importance of emotional and social engagement in promoting sustainable consumer behavior. These results provide managerial implications for marketers to design culturally tailored green marketing strategies that effectively enhance purchase intentions for eco-friendly products.